Development and application of microsatellite markers for genetic diversity assessment and construction of a core collection of Myrciaria dubia (Kunth) Mcvaugh germplasm from the peruvian Amazon - Castro, Juan C. (2024)
The Amazonian shrub Myrciaria dubia (camu-camu) produces vitamin C-rich fruits of growing commercial interest. However, sustainable utilization requires assessment and protection of the genetic diversity of the available germplasm. This study aimed to develop and apply microsatellite markers to assess genetic diversity and construct a core collection of M. dubia germplasm from the Peruvian Amazon. Sixteen polymorphic microsatellite loci were developed using an enrichment approach. The evaluation of 336 genotypes from 43 accessions of the germplasm bank, originating from eight river basins, was conducted using these newly developed markers. Genetic diversity parameters, including observed and expected heterozygosity, were calculated. Analysis of molecular variance (AMOVA) was performed to assess the distribution of genetic variation within and among accessions and river basins. Bayesian clustering analysis was employed to infer population structure. A core collection was constructed to maximize allelic richness. High genetic diversity was observed, with heterozygosity values ranging from 0.468 to 0.644 (observed) and 0.684 to 0.817 (expected) at the river basin level. AMOVA indicated significant genetic variation within (73–86%) compared to among (14–27%) accessions and river basins. Bayesian clustering detected ten genetic clusters, with several degrees of admixture among river basins, except for the genetically homogeneous Putumayo River basin. A core collection comprising 84 plant genotypes (25% of the full collection) was established, representing 90.82% of the overall allelic diversity. These results have important implications for M. dubia conservation strategies and breeding programs, in demonstrating a need for genetic connectivity between populations but preserving unique genetic resources in isolated basins. These results validate the expected levels of diversity and population subdivision in a crop and stress the need to secure genetically diverse germplasms, underscoring the importance of thorough genetic characterization for ex situ germplasm management.